EFFECT OF PARTIAL CEMENT REPLACEMENT RATIO WITH CHICKEN BONE ASH ON COMPRESSIVE STRENGTH AND POROSITY MORTAR - Thresha Sepriany Nainggolan; Karya Sinulingga (Universitas Negeri Medan, 2026)
This study evaluates the effect of partial cement substitution with chicken bone ash on the compressive strength and porosity of mortar. Mortar is a crucial adhesive material in construction that determines the strength and durability of structures. The mortar mixtures were prepared by replacing part of the cement with chicken bone ash at variations of 0%, 3%, 6%, and 9% by weight of the cement according to SNI 03-6825-2002. Cube-shaped mortar samples measuring 5x5x5 cm were tested for compressive strength after 28 days, and porosity was measured using the gravimetric method referring to Archimedes' principle. The compressive strength test results at 0% variation were 10.45 MPa, at 3% variation were 14.75 MPa, at 6% variation were 12.52 MPa, and at 9% variation were 5.52 MPa. The porosity results for the 0% variation were 2.1%, for the 3% variation were 3.2%, for the 6% variation were 3.2%, and for the 9% variation were 4.8%. It is concluded that high porosity can reduce the material's strength. The results of XRF testing on chicken bone ash calcined up to 800°C for 4 hours showed the composition of several chemical elements. Of the elements detected, CaO dominates with a content reaching 61.18%.